'Give them air quickly – don't let them out': Sentencing for manslaughter involving multiple offenders and victims. (October 2021) - Roberts, Julian V
Sentencing for multiple offences poses many challenges and becomes even more complex when the crimes resulted in fatalities. This article uses the sentences imposed following convictions in the Essex lorry case to pose some general questions about the sentencing of multiple victim manslaughters. The four principal offenders were convicted of 39 counts of unlawful act manslaughter and conspiracy to facilitate unlawful immigration into the UK. The analysis identifies several ways in which the sentences ultimately imposed failed to adequately distinguish between offenders of very different levels of culpability. First, all four principal offenders were assigned to the same level of culpability in the manslaughter guideline. Second, although the court could have distinguished the offenders to reflect their different culpability levels, the same Starting Point sentence was imposed on all offenders. Third, the sentencing uplifts to reflect the multiple counts were similar across offenders of very different culpabilities. Fourth, the differential additional punishments for the conspiracy conviction — which would have separated the offenders' time in custody further — were washed out by being made concurrent. As a result of these decisions, the final sentences failed to adequately distinguish between offenders of very different culpabilities. The article concludes with some lessons for sentencing in these cases, specifically with respect to the Sentencing Council's guidelines.